2015
DOI: 10.1097/bpb.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effect on foot and ankle donor site following vascularized fibular graft resection in children

Abstract: This study was carried out to evaluate the long-term effect on the donor side of the foot and ankle following vascularized fibular graft resection in children. Eight patients underwent resection of the fibula for the purpose of a vascularized fibular graft by a surgical team who practiced leaving at least 6 cm residual distal fibula. The age of these children at the time of surgery was between 3 and 12 years. They were reviewed between 3 and 12 years after surgery. Two patients who underwent resection of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Common complications of donor region reported are surgical scar, pain, ankle instability, motor-neural weaknesses, proximal migration of fibula, ankle valgus and deformities of the tibial shaft and ankle [11][12][13][14][15][16][17]. The recommendations of leaving a distal fibular remnant greater than 5-6 cm, distal tibiofibular arthodesis, and scheduling surgical harvest at age older than eight years emerged from these findings [11][12][13][14]. A close examination of literature on the subject showed that a majority of these results surfaced from vascularized fibula graft series where regeneration of donor fibula did not occur.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Common complications of donor region reported are surgical scar, pain, ankle instability, motor-neural weaknesses, proximal migration of fibula, ankle valgus and deformities of the tibial shaft and ankle [11][12][13][14][15][16][17]. The recommendations of leaving a distal fibular remnant greater than 5-6 cm, distal tibiofibular arthodesis, and scheduling surgical harvest at age older than eight years emerged from these findings [11][12][13][14]. A close examination of literature on the subject showed that a majority of these results surfaced from vascularized fibula graft series where regeneration of donor fibula did not occur.…”
Section: Discussionmentioning
confidence: 99%
“…There are only a few studies in the pediatric population to testify for above inferences. Moreover, the main literature for donor site follow-up in the paediatric group has emerged from the vascularized fibular graft technique [11][12][13][14][15][16][17]. An important difference between vascularized and non-vascularized fibular graft is that the donor site following the latter regenerates new bone provided periosteum is preserved, and it can even be used for reharvest.…”
Section: Introductionmentioning
confidence: 98%
“…However, for other patients older than 8 years, no one has ankle or hindfoot deformity. [ 1 ] This strongly indicates that double-cortex fibular graft resection will cause obvious growth deformity in small patients and should not be used in patients younger than 6 years.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional double-cortex fibula graft for adult usually causes severe complications in small patients. [ 1 ] And the studies about effective methods for large bone defect in patients younger than 3 years are rare in literature. In this article, we report a case of 2-year-old boy with a large tibia bone defect treated by ipsilateral single-cortex fibula graft, and it achieves a satisfactory result.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, an additional advantage of our technique is the avoidance of the potential ankle instability and valgus deformity associated with the fibula resection. 11 In addition, by preserving the entire fibula, the longitudinal growth of the fibula is likely to be maintained because the proximal and distal fibular physes are preserved together with the epiphyseal periosteal and endosteal vessels. In fact, after a temporary contraction of the flexor hallucis longus, our patient has shown optimal lower limb function and growth remains symmetrical.…”
Section: Discussionmentioning
confidence: 99%